Gender Household Survey Phase 2 - International Center for Tropical Agriculture; International Food Policy Research Institute (2014)
The purpose of this survey is to gather gender-disaggregated data on agricultural activities, decision-making, weather information, risk-perception and values from rural households. In Phase 2, the gender survey was adapted and implemented in other sites. It was adapted to include some of the production information from IMPACT-Lite since that survey has not been implemented in the new sites. This intra-household survey collects information related to household characteristics, farm production, decision-making, CSA adoption, access to agro-climate information services, etc. from both male and female respondents. This information will be used for researchers, policy-makers and development practitioners to better understand the vulnerabilities of men and women to climate change, how they differ, and what actions can be taken to reduce that vulnerability.